Development of a semi-empirical calibration method by using a LaBr3(Ce) scintillation detector for NORM samples analyses - Ntalla, E.; Markopoulos, A.; Karfopoulos, K.; Potiriadis, C.; Clouvas, A.; Savidou, A. (HNPS Advances in Nuclear Physics, 2021)
In this study, a semi-empirical calibration method for NORM samples measurement by using a LaBr3(Ce) scintillator was developed based on a combination of experimental gamma spectrometry measurements and MCNP-X simulations. The aim of this work is to provide us with full energy peak efficiency calibration curves in a wide photon energy range which is of particular importance when selected photon energies of 234Th, 214Pb, 214Bi, 228Ac, 208Tl and 226Ra are to be measured with accuracy.